Preparation of Copper Oxide Films by Electrochemical Deposition Technique for Extended Gate Field Effect Transistor pH Sensor - Thutiyaporn Thiwawong; Kotchakorn Lertnawanin; Benchapol Tunhoo (My University, 2023)
Abstract In this work, copper oxide (CuO) film was prepared by electrochemical deposition technique on commercial indium-tin oxide/glass substrate with two electrode configuration. The precursor solution was the 0.1 molar aqueous of copper sulfate. The films were prepared at different times of 30 to 120 second. Then, the deposited films were annealed at 450 °C to achieve CuO film. The influence of electro-deposition voltage and deposition times on structural property, morphological features had been studied. The CuO films were used to fabricate the pH sensor based on extended-gate field effect transistor (EGFET). The sensitivity and linearity of prepared device was performed in the standard buffer solutions with pH range of 2-12. It was found that the device demonstrated the sensitivity and linearity of 28.5 mV/pH and 90.1 %. It can be seen that the prepared CuO films can be used as pH sensing application with EGFET device.
Keywords: Deposition; Indium tin oxide; Copper oxide; Electrochemical gas sensor; Analytical Chemistry and Sensors